Research on the Pathways, Policies, and Impacts of Biomanufacturing in Industrial Transformation and Upgrading - Feng, Kehan (Asia Pacific Economic and Management Review, 2026)
As a disruptive paradigm of deep integration between biotechnology and advanced manufacturing, biomanufacturing is becoming a strategic engine for promoting green industrial transformation and cultivating new quality productive forces. This paper systematically studies the pathway mechanisms, policy frameworks, and comprehensive impacts of biomanufacturing in industrial transformation and upgrading. First, it constructs a "technology-industry-policy" co-evolution analysis framework to explain the internal mechanisms driving industrial transformation. Second, it identifies four core pathways: raw material substitution, process innovation, product upgrading, and system integration. Third, it conducts an in-depth analysis of the strategic orientation and implementation mechanisms of the "14th Five-Year" bioeconomy policy, evaluating the layout and synergistic effects of industrial clusters in the Beijing-Tianjin-Hebei region, Yangtze River Delta, Guangdong-Hong Kong-Macao Greater Bay Area, and Chengdu-Chongqing region. Finally, it systematically assesses the comprehensive impacts on industrial restructuring, industrial scale expansion, and sustainable development. The study finds that although China's biomanufacturing industry leads in market scale, it still faces challenges including core technology dependence, slow industrialization, insufficient cost competitiveness, incomplete standard systems, weak industrial ecosystems, and talent shortages. Based on this, the paper proposes recommendations for strengthening top-level design, breaking through key core technologies, improving industrial ecosystems, optimizing regional layout, strengthening talent cultivation, and deepening international cooperation, providing academic support and decision-making references for promoting high-quality development of China's bioeconomy.